Firing Temperature Effects on Phase Formation, Microstructure and Electrical Properties of BNKLT-Sm Ceramics - Metarsit Klinbanmor; Pamornnarumol Bhupaijit; Thitirat Charoonsuk; Panitan Wanakamol; Naratip Vittayakorn; Sarawut Thountom; Theerachai Bongkarn (Integrated ferroelectrics, 2021)
Lead-free Bi0.5(Na0.68K0.22Li0.10)0.5TiO3 + 0.003 mol Sm2O3 (BNKLT-Sm) ceramics were synthesized via the solid-state combustion technique with calcination temperatures between 750 and 850 °C and sintering temperatures between 1025 and 1100 °C for 2 h. The results showed that increasing the calcination temperature caused the percentage of perovskite phase and the particle size of the BNKLT-Sm powders increased. The BNKLT-Sm powder calcined at 800 °C displayed a pure perovskite structure without any impurity phases. The influence of the sintering temperature on the phase formation, microstructure and electrical properties of the ceramics was then investigated. All samples sintered at different temperatures possessed coexisting rhombohedral (R) and tetragonal (T) phases and the R phase became dominant when the sintering temperature increased. The microstructure of all ceramics showed a rectangular shape and anisotropic growth. The average grain size increased with increasing sintering temperature. Dielectric and ferroelectric behavior displayed relaxor characteristics in all samples. The maximum dielectric constant at Tm (εm) of 4777 and the highest remnant polarization (Pr) of 5.03 µC/cm2 were obtained by the densest ceramics (5.85 g/cm3), which was sintered at 1075 °C for 2 h.
Keywords: Ferroelectric and Piezoelectric Materials; Microwave Dielectric Ceramics Synthesis; Multiferroics and related materials